Association between breastfeeding and sleep patterns in infants and preschool children. Issue 6 (28th September 2021) - Abdul Jafar, Nur K; Tham, Elaine K H; Pang, Wei W; Fok, Doris; Chua, Mei C; Teoh, Oon-Hoe; Goh, Daniel Y T; Shek, Lynette P-C; Yap, Fabian; Tan, Kok H; Gluckman, Peter D; Chong, Yap-Seng; et al.
ABSTRACT: Background: Although most studies have reported unfavorable short-term effects of breastfeeding on early-childhood sleep-wake behaviors that potentially attenuate over time, findings have remained inconsistent. Objectives: We assessed associations of breastfeeding with longitudinal day-, night-, and total-sleep trajectories and with sleep-wake behaviors in healthy infants and preschoolers. Methods: Caregivers of naturally conceived, term, singleton infants ( n  = 654) completed the Brief Infant Sleep Questionnaire (3, 6, 9, 12, 18, and 24 mo) and/or Children's Sleep Habits Questionnaire (54 mo), and provided information on their infants' breastfeeding status at 3 mo. Trajectory analyses derived 4 day- ( n  = 243), 3 night- ( n  = 248), and/or 4 total- ( n  = 241) sleep trajectories, each differing in length of sleep duration (short/moderate/long) and variability (variable/consistent). Sleep-wake behaviors from 3 to 24 mo (day/night/total-sleep durations and duration/number of night awakenings) were also assessed for associations with breastfeeding. Results: After adjusting for potential covariates, formula-fed infants, relative to fully breastfed (predominant or exclusive) infants, were significantly less likely to exhibit moderate (OR: 0.28; 95% CI: 0.11, 0.70) and long consistent (OR: 0.18; 95% CI: 0.07, 0.50) night-sleep trajectories and less likely to exhibit moderate (OR: 0.21; 95% CI: 0.07, 0.61) and long consistent (OR: 0.12; 95% CI: 0.04, 0.38) and long variable (OR: 0.16; 95% CI: 0.05, 0.56) total-sleep trajectories, instead of short variable night- and total-sleep trajectories. Partially breastfed infants did not differ from fully breastfed infants for both night- and total-sleep trajectories. No significant differences were found between all groups for day-sleep trajectories. Fully breastfed infants had longer night- (6, 9, 12, and 24 mo) and total- (3 and 12 mo) sleep durations than formula-fed infants, albeit a greater number of night awakenings (from 6 to 12 mo). Conclusions: Despite more night awakenings, fully breastfed infants have overall longer night- and total-sleep durations (sleep trajectories) than formula-fed infants.